A study on the viability of implementing a witness protection programme in Malaysia / Nur Hazwani Shuhaimi ...[et al.] - Shuhaimi, Nur Hazwani; Ramblet, Nur Khairunnisa; Md Zakaria, Siti Nur Hidayah; Zahari, Yasmin (2009)
This research project concerned with the protection of witnesses when they have to face the risk of being harmed by the criminals if they come forward to testify against them. In order to protect the witnesses, one of the effective methods is by setting up a witness protection programme; in other words, by enacting specific law to protect the witnesses. Most of the countries in the world have this kind of programme to protect their witnesses such as United States, Australia, Sri Lanka, Thailand, Philippine and others. As in Malaysia, we do not have specific statute concerning the protection of the witnesses. However, a Malaysian Witness Protection Bill has been tabled for the first reading in Parliament in December 2008. The main objective of this research project is to highlight the important in having specific law, which is Witness Protection Act that will govern protection of witnesses smoothly by set out the methods and procedures to be done by the witnesses and imposed by the responsible authority. It acts as a guideline for the witnesses and responsible authority. Based on our research project, we can conclude that, it is very crucial to have specific law in protecting witnesses because the increasing crimes in our country are becoming more serious. In having Witness Protection Act, the safety of the witnesses are more protected and this will help in upholding justice as more crimes can be settled without the witnesses fear that they will be harmed if they give evidences leading to the arrest of the criminals.